2017
DOI: 10.1155/2017/8913860
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carcinogenesis and Immune Response Gene Polymorphisms: A Review

Abstract: The local immune response is considered a key determinant in cervical carcinogenesis after persistent infection with oncogenic, high-risk human papillomavirus (HPV) infections. Genetic variation in various immune response genes has been shown to influence risk of developing cervical cancer, as well as progression and survival among cervical cancer patients. We reviewed the literature on associations of immunogenetic single nucleotide polymorphism, allele, genotype, and haplotype distributions with risk and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 108 publications
1
37
0
3
Order By: Relevance
“…Our previous study also found that HPV 16, 18, 52, and 58 were the most common types causing cervical cancer among Chinese women . Only a minority of HR‐HPV infections become persistent and finally produces cancerous lesions, suggesting other factors (eg, host immunity and genetic susceptibility) might affect the carcinogenesis . It might take 10‐15 years from the initial HR‐HPV infection to cancer appearance, thus allowing sufficient time for potential cervical screening.…”
Section: Introductionmentioning
confidence: 87%
“…Our previous study also found that HPV 16, 18, 52, and 58 were the most common types causing cervical cancer among Chinese women . Only a minority of HR‐HPV infections become persistent and finally produces cancerous lesions, suggesting other factors (eg, host immunity and genetic susceptibility) might affect the carcinogenesis . It might take 10‐15 years from the initial HR‐HPV infection to cancer appearance, thus allowing sufficient time for potential cervical screening.…”
Section: Introductionmentioning
confidence: 87%
“…We have conducted our methodology according to similar published studies (36,37). A comprehensive, systematic literature search of peer-reviewed, published articles from the NCBI, PubMed, EBSCO, Medline, Elsevier Science, Springer Link and the Google Scholar bibliographic databases was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…HPV16 E5 oncoprotein and downregulation of the surface HLA class I expression has already been reported (78). However, genetic predisposition and variability in the HLA genes, have shown considerable contradictory findings in different study populations (36,79,80). Variations in HLA II genes and cervical cancer susceptibility have been investigated in different geographical populations with inconsistent findings, highlighting the complexity of the viral/host/ environmental ecosystem (69,(80)(81)(82)(83)(84)(85).…”
Section: Ii) Host Hla Polymorphisms Genetic Mutations and Hiv/hpv Comentioning
confidence: 99%
“…Low-risk HPV types include HPV 6 and 11 that have been associated with benign anogenital warts. At least 12 HR-HPV types, HPV 16,18,31,33,35,39,45,51,52,56, 58 and 59, have been associated with anogenital cancers as well as precursor neoplastic lesions [8]. It is now established that HPV 16 and 18 are the major papillomavirus types responsible for cervical cancer.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Cervical carcinoma, which is caused by malignant transformation of cervical epithelial cells following persistent HPV infection, is one of the most common malignant cancer among women, approximately 10% of all cancers in the female population [31]. The relationship between HPV and cervical cancer is observed in many studies, and the persistent infection of the HPV carcinogenic types is found to be the cause in about 90-100% of the cases.…”
Section: Cervical Cancermentioning
confidence: 99%